Variegated Capitalism as an approach for understanding globalisation in the wake of COVID-19 - Lukas Handley; Anne Martin (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2025)
The various social and economic crises triggered by COVID-19 have revealed and reflected the many forms of contradictions, interdependencies and power asymmetries that underpin our current form of globalised capitalism. While Comparative Capitalisms approaches can provide useful insights into how national economies mediate crisis and how external forces can lead to shifts within domestic economies, these frameworks struggle with various theoretical and methodological limitations. This paper instead argues that Variegated Capitalism is better suited to analysing the effects of COVID-19 and, importantly, to understanding the COVID-19 crisis at a systemic level, by engaging with and integrating these levels of analysis in a wider examination of capitalism as a hegemonic global system. With this, we also aim to demonstrate that Variegated Capitalism provides an ambitious framework for analysing moments of globalised capitalism beyond the current conjuncture.
Keywords: P00; B51; F60; 330; variegated capitalism; Comparative Capitalisms; COVID-19; globalisation; crisis